New data on lithic technology of Early Neolithic in Northern Italy: refittings from Lugo di Grezzana (VR) - Fabio Santaniello; Vanya Delladio; Anna Ferrazzi; Stefano Grimaldi; Annaluisa Pedrotti (IpoTESI di Preistoria, 2020)
Lithic technology is an uncommon research tool for investigating the Neolithic lithic industries of northern Italy. In fact, our knowledge about the lithic industries of this period is mainly related to typological descriptions. The technological study of these fittings found in the Lugo di Grezzana (VR) site highlights the usefulness of this approach and provides evidence to detect technical skills and socio-economic relationships among the early Neolithic groups.